2017
DOI: 10.1177/1077699017723604
|View full text |Cite
|
Sign up to set email alerts
|

The Spillover Effects of Political Scandals: The Moderating Role of Cynicism and Social Media Communications

Abstract: This study examines how political cynicism and social media communications moderate the spillover effects of political scandals, that is, the extent to which a scandal surrounding one political figure may influence people’s attitudes toward other political objects. Theoretically, spillover effects are understood as grounded in how people understand the interconnections among politicians and institutions. Analysis of a representative survey in Hong Kong documents the presence of spillover effects of scandals su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 42 publications
6
39
0
1
Order By: Relevance
“…In line with previous research (e.g., Lee, 2018), spillover effects can generally be explained with the help of the accessibility-diagnosticity framework. The framework is based on spreading activation theory (Collins & Loftus, 1975) and postulates that people use implicit theories on how particular things are related in the world.…”
Section: Spillover Effects Of Political Hypocrisysupporting
confidence: 74%
See 4 more Smart Citations
“…In line with previous research (e.g., Lee, 2018), spillover effects can generally be explained with the help of the accessibility-diagnosticity framework. The framework is based on spreading activation theory (Collins & Loftus, 1975) and postulates that people use implicit theories on how particular things are related in the world.…”
Section: Spillover Effects Of Political Hypocrisysupporting
confidence: 74%
“…We used two separate models to examine the specific newspaper article's effect on the two outcome variables: Green Party attitude and Green Party voting intention. Also, previous research has clearly shown that partisanship affects political evaluations in the context of political scandals (Fischle, 2000;Lee, 2018). Therefore, we controlled for participants' prior Green Party identification to ensure that all effects were assessed independently of their prior party identification.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations